Development of Gamified Higher-Order Thinking Skills Assessment Items for Phase D Informatics through Pedagogical Deep Learning - Uswatun Hasanah; Syahrul; Anas Arfandi (ISEJ : Indonesian Science Education Journal, 2026)
This study developed and evaluated gamified Higher-Order Thinking Skills (HOTS) assessment items for Phase D Informatics through a pedagogical deep-learning orientation. The research addressed the limited availability of valid, reliable, and practical digital assessment instruments capable of measuring students’ analytical and evaluative thinking in junior secondary Informatics. A Research and Development design was employed by integrating the ADDIE, 4-D, and Tessmer formative-evaluation models into five stages: needs analysis, product design, development and validation, implementation and evaluation, and finalization. The product consisted of 20 contextual multiple-choice items delivered through Quizizz and designed according to Phase D Informatics learning outcomes and the principles of mindful, meaningful, and joyful learning. Content, assessment, and language validation involved three experts, while field testing involved 60 Grade VIII students from three public junior secondary schools in Pinrang Regency, Indonesia. Data were collected using validation sheets, assessment responses, observation records, and teacher and student practicality questionnaires. The results showed an overall expert-validation score of 94.24%, indicating that the instrument was highly valid. Empirical item analysis identified 17 valid items, while three items required substantial revision. The instrument demonstrated acceptable internal consistency, with a Cronbach’s alpha of .735. Most items showed moderate difficulty and adequate-to-good discrimination. Teacher and student responses produced a combined practicality score of 86.81%, categorized as highly practical. These findings indicate that gamification can support the delivery of evaluated HOTS assessment in Phase D Informatics.